The Application of Knowledge Graph in Higher Mathematics Teaching - Xu, Qian; Zhao, Ye (Journal of Educational Research and Policies, 2025)
Higher mathematics is characterized by many knowledge points, complex relations and strong logic. In order to help students sort out the internal relations between knowledge points, and visually display the relations between knowledge points, knowledge graph is applied to the teaching of higher mathematics. Based on the analysis of the related knowledge of knowledge graph, by using the tools such as protégé and python, this paper expounds the construction and application of knowledge graph in higher mathematics. Taking the higher mathematics course of Beijing union university as an example, the teaching practice shows that enabling higher mathematics teaching through knowledge graph can effectively improve students' academic performance, and also shows the effectiveness of knowledge graph construction.